Teacher´s role in the meaningful learning achievement based on ICT (Encuentros, 2019)
n this paper, we analyze the role of the teacher that seeks in students the development of competences, such as those formulated by critical didactics for the development of knowledge, skills and values; which should be supported in the proper use of Information and Communication Technologies, in order to facilitate learning that is meaningful and useful in their family, social and work context; likewise, it invites to the discussion on how from educational practices access to the construction of knowledge in a critical, argumentative, proactive and communicative way, where the interests of each subject that intervenes in the educational process, focuses on learning. Similarly, teacher´s role in the development of meaningful learning is exposed with the approach to knowledge that today allow the means of communication and information, which aims to strengthen the teaching-learning process from the interests, needs and opportunities presented the contextKey words: Significant Learning; Information and Communication Technologies; Competencies; Educational Process.